Costeo ABC y su efecto en los estados financieros de la empresa M & D E.I.R.L. distrito Chepén, año 2020 - Quiroz Villoslada, Geiner Jossmel (2021)
The present research work was carried out with the purpose of studying the road freight transportation service sector in the district of Chepén and determining the effect of ABC costing in the financial statements of the company M & D Individual Limited Liability Company, year 2020. For its development an inductive - deductive method was used, which is characterized by a first stage of induction of explanatory principles from an observed problematic reality and a second stage that contains a theoretical body related to the problematic reality under study. For this purpose, data collection techniques and instruments such as interviews and documentary analysis were used. For the treatment of information, tables and graphs were used, with the purpose of being adequately understood and interpreted. The research population is represented by the cargo transportation company M & D Individual Limited Liability Company.in the district of Chepén. The sample is conformed by the administrative, accounting and financial information provided by the accountant and owner of the company. The conclusions obtained in the research are that ABC costing has a positive effect on the financial statements of the company M & D Individual Limited Liability Company; and that ABC costing determines the true total cost of the service and the correct classification of costs.